Spatial targeting of small-scale ruminant silvopastoral systems in Ghana - Nanjala, Catherine Topister; Van Der Hoek, Rein; Notenbaert, An (2025)
This study aims to assess the spatial suitability for piloting silvopastoral systems in Ghana using an interactive tool: The Land Targeting Tools.